INTEGRASI HUKUM ISLAM DAN ADAT JAWA ATAS HARTA WARIS BAGI ANAK ANGKAT - Sakirman, (IAIN Tulungagung, 2018)
The status of adopted children in Islamic law and Javanese customs is still an interesting phenomenon to be studied in Islamic studies, especially to know the legal consequences of two dimensions, namely Islamic law and Javanese customs. Indeed, children are mandates that can be nurtured both physically and mentally by both parents. A child is worthy of life with all the needs sought by both parents as a form of responsibility. However, these conditions often cannot be felt by some children because one or both of their parents died. On that basis, it can cause a childs life condition no longer like a child in general who still has biological parents. Another problem arises from the possibility that both parents are not economically capable to finance their childrens lives. Thus, other children are taken to be adopted by other people. Child adoption ultimately has legal consequences for inheritance. In time the adopted child can be counted as a person who has the right to get the property of the adoptive parent after death and the existence of the adopted child has a position of inheritance. The method in this study uses a review of pure literature using analytical content. The final results of non-finalÂ writing indicate that according to Javanese custom, adoption of a child does not break the childs relationship with biological parents and adopted children nor are they biological children of adoptive parents, but adopted children are entitled to inheritance from their parents and also from people adoptive old man. Whereas according to Islamic law, cannot accept the existence of adopted child status over his position of inheritance from adoptive parents.Keywords: Javanese customs, inheritance, adopted children, Islamic law